ANALISIS KORELASI HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA KLINIK SKINCARE (STUDI PADA KLINIK PUSPITA PRINGSEWU) - Gumanti, Miswan; Utami, B. (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
This study aims to analyze the correlation between price, product quality and service quality variables on consumer satisfaction at the Puspita Pringsewu skincare clinic. The results of this study are expected to help Puspita Pringsewu Beauty Clinic in determining the steps of a marketing strategy that is oriented towards increasing consumers who use services and products. The results of the analysis show that each of the price, product quality, and service quality variables has a positive correlation with the consumer satisfaction variable.Keyword: price, product, service, skincare clinic